AMELOTEX IN THE TREATMENT OF CHRONIC BACK PAIN SYNDROMES - Irina Yuryevna Suvorova (Современная ревматология, 2010)
Recently there has been a considerable increase in the number of patients with lingering recurrent and chronic pain syndromes of various origin. Forty-one patients with dorsopathies were examined. Two types of pain were identified; these were vertebrogenic and nonvertebrogenic pains. The appropriateness of this identification was confirmed by instrumental studies. Treatment was performed using a selective nonsteroidal antiinflammatory drug (Amelotex). Pain syndrome relief was noted during the therapy